Protecting the Mental Health of Small-to-Medium Enterprise Owners: A Randomized Control Trial Evaluating a Self-Administered Versus Telephone Supported Intervention. Issue 7 (July 2020) - Martin, Angela; Kilpatrick, Michelle; Scott, Jenn; Cocker, Fiona; Dawkins, Sarah; Brough, Paula; Sanderson, Kristy
Abstract : Objective: Small-medium enterprises (SMEs) are under-represented in occupational health research. Owner/managers face mental ill-health risks/exacerbating factors including financial stress and long working hours. This study assessed the effectiveness of a workplace mental health and wellbeing intervention specifically for SME owner/managers. Methods: Two hundred ninety seven owner/managers of SMEs were recruited and invited to complete a baseline survey assessing their mental health and wellbeing and were then randomly allocated to one of three intervention groups: (1) self-administered, (2) self-administered plus telephone, or (3) an active control condition. After a four-month intervention period they were followed up with a second survey. Results: Intention to treat analyses showed a significant decrease in psychological distress for both the active control and the telephone facilitated intervention groups, with the telephone group demonstrating a greater ratio of change. Conclusion: The provision of telephone support for self-administered interventions in this context appears warranted.